Consequences of an Analysis Using Biblical Analogies for Automated Vehicle Control Design - Balázs NÉMETH (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2022)
The paper proposes an analysis of learning-based approaches for automated vehicle control systems from an ethical viewpoint. An analysis using analogies between selected biblical texts and operation concepts of learning-based approaches is per-formed. Thus, analogies for supervised, unsupervised, and reinforcement learning-based approaches are created. Through the analogies, the root of the automatic control design problems, i.e. forming objective functions, on a theological level is explored. The analysis leads to three consequences, which are related to the difficulty of forming control objective, the difficulty of considering human objectives in control, and the necessity of viewing systems in all their complexity. The paper proposes the application of the consequences in an illustrative route selection vehicle control example. A multi-layer control concept involving the consequences of the analysis is proposed, with which some ethical challenges of the selected control problem can be handled.